Determinanty doboru informatycznego systemu budżetowania - Kes, Zdzisław; Nowosielski, Krzysztof (The Determinants of Matching Budgeting Computing Systems, 2008)
The paper presents the problem of matching budgeting IT systems. It discusses several determinants of choosing proper IT systems as for example enterprise size and structure, types and number of budgets, types of responsibly centres. Each determinant was briefly described.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 31-37